Customers’ Preference for a Beach Resorts in East Coast Davao Oriental: A Conjoint Analysis - Losentes , Roneth; Schneider, Stilo Floyd (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study analyzed customer preferences for beach resorts on the East Coast of Davao Oriental using conjoint analysis. It was anchored in Consumer Behavior Theory, Random Utility Theory, revealed-preference theory, and Howard’s Theory of Consumer Problem Solving, which collectively explain how customers evaluate service attributes and make trade-offs in selecting tourism offerings. The study employed a quantitative-descriptive, cross-sectional design and involved 300 purposively selected domestic vacationers and non-resident beach visitors who had visited or planned to visit beach resorts in Cateel, Baganga, and Caraga. Data were gathered through a structured survey questionnaire that included demographic profiling, conjoint analysis tasks based on 20 hypothetical resort profiles, and a 5-point preference scale. Key informant interviews and pilot testing were conducted to refine the instrument, and the data were analyzed using descriptive statistics, part-worth utility estimation, and relative importance scoring. The findings revealed that location was the most important resort attribute, followed by booking facility, amenities, and accommodation. Respondents most preferred resorts located near the beach, booked through a travel agency, offering premium amenities, and providing family villa accommodation. The results also showed variation in individual preference patterns, although the aggregate model confirmed a dominant market preference for convenience, accessibility, and enhanced resort experiences. The most preferred resort profile combined the highest-valued attribute levels, while the least preferred profile reflected less attractive combinations of features. The study concluded that resort operators should use these findings to improve service design, strengthen booking systems, refine marketing strategies, and enhance accommodation features, particularly standard rooms. It also recommended future studies with larger samples and additional resort attributes. The study aligns with SDG 8 (Decent Work and Economic Growth), SDG 11 (Sustainable Cities and Communities), and SDG 12 (Responsible Consumption and Production) because it supports tourism competitiveness, place-based planning, and more responsive resort development. Its sustainability impact lies in providing evidence-based guidance for socio-economic, community, institutional, and tourism sustainability in emerging coastal destinations.